The development of Road Safety Courseware (RSC) for primary school students / Erme Razme Asyilah Ahmad Termeze - Ahmad Termeze, Erme Razme Asyilah (2022)
Multimedia applications are utilised in education as a source of data to provide students with learning tools. Applications that use multimedia are also used to enhance learning and boost interaction between students and lecturers or teachers. the problem that arose at Sekolah Kebangsaan Kind Edward VII (2) was that children were more vulnerable to other road users because they lack road safety experience. In addition, there are still children who practice dangerous behaviors on the road, use incorrect road positions and playing while on the road and the knowledge of road safety among parents is unsatisfactory because they assumed that the children aged 10 and below, know how to cross, understand about traffic lights very well and know about the position of the road well. So that, to enable students, receive greater exposure to PKJR through the development of this project, Nielson's Ten Heuristics Principles were used to develop the Road Safety Courseware (RSC). The research objectives are to identify the requirements of road safety courseware for the primary school students, to design and develop road safety courseware for the primary school students and to evaluate the user acceptance test towards the Road Safety Courseware. The RSC courseware created for students aged eight which is for Year 2 students. The ADDIE model was used to create the project. Five phases comprise this model: analysis, design, development, implementation, and evaluation. Three experts and 30 potential users are evaluating RSC. The developer project was tested by a single end user and the developer. Five categories comprise the user evaluation construct: usability, multimedia elements, navigation, content, and activities. The evaluation result indicates that respondents are satisfied with the courseware's usability, with a mean of 4.5 and a standard deviation of 0.61. By implementing this courseware, students will gain a better understanding about road safety. The recommendations for future improvement are adding more activities and games and improve the skills in making video so that user can watch the video attractively. Lastly, developer want to make this courseware offline so that all users can access this eLearning easily.